The Thought-Scene: A Literary Convention of Hebrew Narrative - Keefer, Arthur (Journal of Hebrew Scriptures, 2024)
There is an unidentified literary convention within narratives of the Hebrew Bible, wherein the narrator portrays the thought process of certain characters. In these episodes, which I coin “thought-scenes,” characters express the motivating reasons for a past, current, or upcoming action. That is, they explain “why” an action, decision, or request is being undertaken. These passages constitute distinctive instances of human reasoning and offer insight into how rationality was viewed in the ancient world, as well as how forms of argumentation were fashioned within biblical literature. I examine the reasoning process of Abraham (Gen 12:10-20) and Joseph (Gen 39:7-10) in detail and supply a full, annotated catalogue of thought-scenes in Genesis, along with representative examples from across the Hebrew Bible.